Olympic athletes and officials ponder vaccine dilemma as Tokyo Games loom - Pender, K. (The Guardian, 2021)
teve Solomon, a 400-metre sprinter and co-captain of the Australian athletics team, has plenty to think about. The postponed 2020 Olympics are now just six months away and, barring a Covid-19 outbreak in Australia, Solomon will compete in the national championships in April before beginning final preparations for Tokyo. But there is one thing that the sprinter insists is not front of mind for him and his teammates: the coronavirus vaccine. "Everyone is just focused on making sure we are physically and mentally ready for the Games," he said.